Causes of deformations of buildings and structures - Aitkozhin Азамат (Рroblems of engineering and professional education, 2023)
Accidents and deformation of buildings and structures is not so much due to errors in the calculation of the above-ground engineering structures, but because of the mistakes admitted in the design (approximately 18%) and construction (80%) of foundations. Experience shows that structural damage or accident buildings rarely occur for any one reason. This is usually the result of the interaction of many factors, one of which can play a decisive role. Establishment of the main reasons for building deformation is quite challenging, the resolution of which requires specialist mainstreaming work building structure and its foundation, as well as a thorough examination of the circumstances that caused the development of strains